Lay Associations of Christ's Faithful and the Church's Response to Allegations of Sexual Abuse - Pagé, Roch (The jurist, 2024)
ABSTRACT: For more than two decades, since the promulgation of the motu proprio Sacramentorum sanctitatis tutela in 2001, several official documents were published by the Holy See and different conferences of bishops (e.g., the Canadian Conference of Catholic Bishops) concerning sexual abuse of minors or persons having the imperfect use of reason. Only clerics were addressed under that law. Since the publication of the revised Book VI on penal law, members of religious institutes of men and women together with any member of the faithful performing a function in the Church are included among alleged perpetrators of sexual abuse of minors. After reviewing all the official documents, the author notes that members of lay associations of Christ's faithful are not mentioned anywhere as alleged perpetrators of sexual abuse of minors. Even the members of public associations of Christ's faithful whose mission is fulfilled in the name of the Church in virtue of their status of public juridical persons are not included. Some suggestions are offered to diocesan bishops for how to take into account the members of lay associations of Christ's faithful in their diocesan protocols.